2017
DOI: 10.1016/j.still.2016.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Corn stover harvest and tillage impacts on near-surface soil physical quality

Abstract: and Cherubin, Maurício R., "Corn stover harvest and tillage impacts on nearsurface soil physical quality" (2017). Publications from USDA-ARS / UNL Faculty. 1628Faculty. . http://digitalcommons.unl.edu/usdaarsfacpub/1628 Corn stover harvest and tillage impacts on near-surface soil physical quality Excessive harvest of corn (Zea mays L.) stover for ethanol production has raised concerns regarding negative consequences on soil physical quality. Our objective was to quantify the impact of two tillage practices a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
49
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 61 publications
(95 reference statements)
9
49
1
4
Order By: Relevance
“…The LLWR was computed following the guidelines described by Wu et al (2003) and used by Tormena et al (2017). SWRC and soil PR curve (SPRC) fittings were done according to the method of Moreira et al (2016) and following the procedure described by Regazzi and Silva (2004).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The LLWR was computed following the guidelines described by Wu et al (2003) and used by Tormena et al (2017). SWRC and soil PR curve (SPRC) fittings were done according to the method of Moreira et al (2016) and following the procedure described by Regazzi and Silva (2004).…”
Section: Methodsmentioning
confidence: 99%
“…The impact of SPQ on plant development is often assessed by using several of the single soil physical indicators (Betioli Júnior et al, 2012;Guimarães, Ball, Tormena, Giarola, & da Silva, 2013;Mukherjee & Lal, 2014). The least limiting water range (LLWR) is an SPQ indicator that integrates water availability, aeration, and soil resistance into a single index, which provides a better understanding of the physical behaviour of a range of soils under different FSs around the world (de Lima, Miola, Timm, Pauletto, & da Silva, 2012;Guimarães et al, 2013;Tormena, Karlen, Logsdon, & Cherubin, 2017). Crops under NT system can overcome the higher soil penetration resistance (PR) than can those under ploughed soils.…”
mentioning
confidence: 99%
“…Structural degradation of soils induced by crop residue harvest is related to decreased macro-aggregation and aggregate stability (Wegner et al, 2015;Johnson et al, 2016), which consequently lead to soil compaction (Wilhelm et al, 2004;Roque et al, 2010). Soil compaction decreases macroporosity and increases mechanical resistance to root penetration (Rosim et al, 2012;Tormena et al, 2017), which decreases water availability to plants (Tormena et al, 2017).…”
Section: Ii) Crop Residues Vs Soil Physical Propertiesmentioning
confidence: 99%
“…Moreover, the maintenance of crop residues favors infiltration Johnson et al, 2016;Valim et al, 2016) and storage of water in the soil (Peres et al, 2010;Xiukang et al, 2015;Tormena et al, 2017). Peres et al (2010) observed that the presence of 15 Mg ha -1 of sugarcane straw covering the soil reduced water loss (0-20 cm layer) by approximately half when compared to uncovered soil.…”
Section: Ii) Crop Residues Vs Soil Physical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation